A STUDY ON PRODUCT PACKAGING ON CONSUMER BEHAVIOUR OF FMCG PRODUCTS (A STUDY WITH REFERENCE TO KRISHNAGIRI CITY) - Sumithra P; Priyadharisini, Mary J (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study is to look into important factors that make a customer satisfaction program successful. This study also shows how the independent and dependent variables relate to one another. Questionnaires were used to collect data for this primary investigation, and SPSS software was used to make study-related decisions. In this study, samples of 250 respondents were used to test the accountability of the model. Packing is the most important component, according to the research study's evaluation. It follows that when consumers are making any kind of purchase, packaging elements like material, wrapper design, and revolt are more important factors to take into account. And now, at last, it has ended.